STRATEGI DAKWAH AMIL DALAM MEMBERIKAN BIMBINGAN PRA-NIKAH PADA CALON PENGANTIN DI DESA SERUMPUN BULUH KECAMATAN TEBAS KABUPATEN SAMBAS - Dede Kurniawan; Deni Irawan; Enik Sartika (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The purpose of this study was to find out about the amil da'wah strategy in pre-marital guidance, the supporting and inhibiting factors in providing pre-marital guidance and the implications of pre-marital guidance in the village of allied reeds, Tebas District. This study uses a qualitative approach with a descriptive type. The results of the study found that coaching efforts in the process towards a pre-marital sakinah family are important because this is a building, if the building is solid and strong then a strong foundation must be made. The pre-marital guidance steps are by filling out the BP4 form by the bride and groom and correcting if there are errors in the BP4 requirements and the existence of an agreement to be serious in living married life. Supporting and inhibiting factors in the guidance process are apart from the influence of educational background and family influence, social media also has an effect on the supporting process in pre-marital guidance. The inhibiting factor in the pre-marital guidance process is the difference in the views of one's sect and for the bride and groom who are less fluent in reading the Qur'an and less in memorizing the prayers delivered by Amil.